La desinformación como una forma de injusticia social - de la Puente, Carlos Alberto (2025)
In this essay I argue that the practice of disinformation is a form of social injustice, since it is an attempt to harm the individual´s capacity to participate in the democratic process of discussion of public issues. After reviewing the importance that truth has in the life of individual and communities and surveying, following John Dewey, the concept of the public, I posit that to disinform, that is to intentionally propagate false information regarding a topic of public interest, constitute an attack on the dignity of the person, since this dignity is grounded on the individual´s ability to engage in the justification of social and political norms.